2012
DOI: 10.1007/s10103-012-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of temperature elevation on human teeth root surfaces during Nd:YAG laser irradiation in root canals

Abstract: The purpose of this study was to evaluate the temperatures on the root surfaces during Nd:YAG laser irradiation in root canals using pulse durations of 180 and 320 μs. Thirty extracted human teeth were used in this study. The teeth were enlarged up to ISO 40 (multi-rooted) or up to ISO 60 (single-rooted) by conventional technique using K-files. Then the teeth were placed into a water bath with a constant temperature of 37 °C and then irradiated with an Nd:YAG laser having an output power of 1.5 W, a frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In the present study, the temperature reached generally higher values in the apical thirds of the specimens, followed by those of the middle and cervical thirds. The results are in agreement with Strakas et al (2013), who stated that the difference between the mean values for pulse duration differences is higher for apical points followed by those of mesial and coronal points [35]. In contrast, Falkenstein et al (2014) found that the highest values for ΔTmax were in the middle of the root [30], due to the movement of the fiber tip which was guided parallel to the root surface in a constant horizontally swinging movement (∼ 2 mm).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the temperature reached generally higher values in the apical thirds of the specimens, followed by those of the middle and cervical thirds. The results are in agreement with Strakas et al (2013), who stated that the difference between the mean values for pulse duration differences is higher for apical points followed by those of mesial and coronal points [35]. In contrast, Falkenstein et al (2014) found that the highest values for ΔTmax were in the middle of the root [30], due to the movement of the fiber tip which was guided parallel to the root surface in a constant horizontally swinging movement (∼ 2 mm).…”
Section: Discussionsupporting
confidence: 90%
“…It was previously reported that Nd:YAG laser at 100 Hz/ 15 W caused an average temperature elevation of <9°C on the root surfaces and, according to the authors, this temperature change would cause minimal damage in bone and periodontal tissues (Strakas et al 2013). 29 As the present study used 15 Hz/1.5 W for Nd:YAG lasers, the temperature increase on the root surface woud have been minimal.…”
Section: Discussionmentioning
confidence: 77%
“…It was previously reported that Nd:YAG laser at 100 Hz/15 W caused an average temperature elevation of less than 9 °C on the root surfaces and this temperature change would cause minimal damage in bone and periodontal tissues (20). As the present study used 15 Hz/1.5 W for Nd:YAG lasers, the temperature increase on the root surface would be minimal.…”
Section: Discussionmentioning
confidence: 86%